Wild pollination services to California almond rely on semi-natural habitat - Klein, Alexandra-Maria; Brittain, Claire; Hendrix, Stephen D.; Thorp, Robbin; Williams, Neal; Kremen, Claire (The Journal of applied ecology, 2012)
1. Global declines in honeybees have led to concerns about negative impacts on food production because of low levels of pollination. This is exemplified in California where the demand for honeybees Apis mellifera to pollinate almond Prunus dulcis is increasing, but problems with honeybee health suggest it may not be sustainable to rely solely on the pollination service of a single species. 2. We investigated the effect of the quantity of surrounding natural habitat, organic management and strips of semi-natural vegetation on flower visitation frequency of wild and managed pollinators and fruit set in 23 California almond orchards (15 conventional, 8 organic). Five conventional and four organic orchards were surrounded by a low percentage (< 5%) of natural or semi-natural habitat in a 1-km radius and another five conventional and four organic orchards were surrounded by a high percentage of these habitats (> 30%). A further five conventional orchards with a low percentage of surrounding natural habitat had an adjacent strip of semi-natural vegetation and were included in the study to represent a realistic option for orchard management in intensive agricultural landscapes. 3. Wild bee species visited almond flowers but only in orchards with adjacent semi-natural habitat or vegetation strips. Organic management increased the flower visitation frequencies of hover flies and wild bees. The presence of a strip of semi-natural vegetation in orchards with a low percentage of surrounding natural habitat increased the number of species and the flower visitation frequency by wild pollinators but only at orchard edges and not to the degree seen when natural habitat was abundant. 4. Wild bee species richness and flower visitation frequency, but not honeybee frequency, were related to fruit set. Fruit set increased with increasing percentage of natural habitat surrounding the orchards. Organic farming or the presence of a vegetation strip did not increase fruit set. 5. Synthesis and applications. The restoration of high quality habitat strips along the edges of crop fields in highly intensified agricultural landscapes should be encouraged and monitored to conserve pollinators and to determine whether benefits for agriculture can be realized. Although honeybees are the main and most important pollinating insects for many plants, wild pollinators may be necessary to ensure high fruit set. Organic farming alone will not sustain wild pollination services for almond in California.